Pengaruh Disiplin Kerja, Motivasi dan Kepemimpinan Terhadap Kinerja ASN Dinas Pekerjaan Umum Bina Marga dan Tata Ruang Provinsi Sumatera Selatan - Melli Haryani; Muhammad Idris; Diah Isnaini Asiati (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of work discipline, motivation and leadership jointly on the performance of ASNs at the Department of Public Works, Highways and Spatial Planning, South Sumatra Province. To determine the effect of work discipline on the performance of ASN at the Department of Public Works, Highways and Spatial Planning for the Province of South Sumatra. To determine the effect of motivation on the performance of ASN Public Works Department of Highways and Spatial Planning of South Sumatra Province. To find out the influence of leadership on the performance of ASN at the Department of Public Works, Highways and Spatial Planning for the Province of South Sumatra. This type of research is associative. The sample in this study was 151 respondents with a sample collection technique using the Cluster Sampling technique (sample area). The data used in this study are primary data, namely the number of respondents, agency profiles and secondary data collection methods, namely the questionnaire. The analysis technique used is multiple linear regression analysis. The results showed that: (1) there is a significant influence of work discipline, motivation, and leadership variables together on performance (2) Work discipline does not have a significant effect on performance (3) Motivation has a significant effect on performance (4) Leadership has influence on performance.